Rainfall induced residual soil slope instability: building cracked and slope failure - L. J., Yue; Mohd Fakhrurrazi, Ishak; M. S. I., Zaini; M. F., Zolkepli (IOP Publishing, 2019)
Rainfall is one of the factors of slope failures due to the intensity of rainfall that will seep and increase the moisture content of geo-materials. One of the important role in slope stability is matric suction. This study present the relationship between rainfall and suction of soil which induced the slope instability and the slope stability analysis involving a building which may cause by instability due to suction variation. The slope had separated into three parts which are top of slope, middle of slope and toe of slope. Every part has been inserted with three tensiometer with 0.3 m, 0.45 m and 0.9 m depth. Suction of soil on slope was carried out by using tensiometer. Intensity of rainfall was collected by using rain gauge which placed at open area which to compare with matric suction of soil. Several site and laboratory tests were carried out to identify the soil properties. Stability of slope was analyzed using Slope/w and Manual Calculation via input parameters collected from laboratory test and field test. Fellenius’ method was used to interpret the factor of safety for slope study. This includes the analysis of the factor of safety of slices at the selected area with its matric suction value. It was found that when the rainfall increased, the suction of soil decreased and affected to decrease of factor of safety. Hence, the constructed slope was suggested to be redesign to improve its safety factor.